Phonetic Transcription Development in KBBI: The Study of Structural Linguistic - Sujarno (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This research aims to describe the development of The Great Dictionary of the Indonesian Language (abbreviated in English and Indonesian as KBBI) according to phonetic symbol. The data of this qualitative study is the development of KBBI covering phonetic symbol. This research used structural linguistics theory. Specially, the theory includes phonetic symbol. The method of this research is descriptive qualitative research. The data were taken from KBBI I up to KBBI IV which were collected through analysis and documentation from 2013 until 2015. As for the data analysis technique, this study used content technique analysis (reading the data source, comparing, analyzing, interpreting, assigning, and concluding). The result of the study of the development of Kamus Besar Bahasa Indonesia based on phonetic symbol showed no development, because in KBBI I until KBBI IV there is only sound development [é]. Structurally in KBBI I until KBBI IV not showed the realization of phonetic symbolThis study provides suggestions for experts compiling the dictionary content, educational institutions’ leaders (school headmasters, Rectors, Head and Director of Institutions), head of libraries, teachers or lecturers, and dictionary users.